The Antarctic ozone hole: An update - Douglass, Anne R.; Newman, Paul A.; Solomon, Susan (Physics Today, 2014)
In the 30 years since the ozone hole was discovered, our understanding of the polar atmosphere has become much more complete. The worldwide response to the discovery was fast, but the recovery is slow.